1999
DOI: 10.1007/bf02355611
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion strength of polymer-containing protective coatings

Abstract: The use of composite coatings based on a polymer matrix and inorganic fillers is a real way of protecting the working parts of technological equipment against corrosion and wear in chemical, petroleum processing, and food industries. The important factors which define wear and corrosion resistance of coatings are the chemical stability of every component and the bond strength on the "polymer-filler" interface [ 1,2]. As a polymer matrix in the creation of coatings, it is promising to use epoxy low-molecular re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Fang and Shijun 8 , on the other hand, investigated the mechanical and thermal properties of hard PVC after the addition of red mud, and they indicated that these materials could be used in decorative household applications. Moreover, Kal'ba et al 9 examined the possibility of red-mud-reinforced epoxies being used in corrosion-resistant composite coating applications.…”
Section: Introductionmentioning
confidence: 99%
“…Fang and Shijun 8 , on the other hand, investigated the mechanical and thermal properties of hard PVC after the addition of red mud, and they indicated that these materials could be used in decorative household applications. Moreover, Kal'ba et al 9 examined the possibility of red-mud-reinforced epoxies being used in corrosion-resistant composite coating applications.…”
Section: Introductionmentioning
confidence: 99%
“…This causes a considerable plastic deformation of material. In can be asserted that the system of such composites has a low cohesive strength, which is corroborated by investigations [14][15][16][17][18]. The return of specimen to its original shape after unloading is evidence of elastic properties of material and hence of its high cohesion characteristics.…”
mentioning
confidence: 51%
“…The formation of constructional materials, including polymer ones, with the necessary complex of improved properties is an important problem for today [1][2][3][4][5][6][7][8][9][10][11][12]. This problem is solved by selecting a range of fillers content in materials, which is achieved using the method of mathematical statistics.…”
Section: Statement Of the Problemmentioning
confidence: 99%